On Nadia Urbinati, Democracy Disfigured: Opinion, Truth, and the People and Pierre Rosanvallon, The Society of Equals - Bashkina, Olga (Stasis, 2016)
Book review:Nadia Urbinati, Democracy Disfigured: Opinion, Truth, and the PeopleCambridge, MA: Harvard University Press, 2014, 320pp., ISBN 978-0674725133Pierre Rosanvallon, The Society of EqualsCambridge, MA: Harvard University Press, 2013, 384pp., ISBN 978-0674724594